Election campaigns, agenda setting and electoral outcomes - Manfred Holler; Peter Skott (University of Massachusetts, Department of Economics, 2004)
Framing effects and bounded rationality imply that election campaigns may be an important determinant of election outcomes. This paper uses a two-party setting and simple game theoretic models to analyse the strategic interaction between the parties campaign decisions. Alternations of power emerge naturally, even if both electoral preferences and party positions remain constant.
Keywords: D72; 330; Election; campaign platforms; agenda setting; cost of ruling; Condorcet